Audit Fee Determinants for SMEs - Evidence from Shen Zhen, China - Kai, Zhu (2009)
The research on determinants of audit pricing has never stopped since the first study published in 1980. The surge of Chinese small and medium enterprises listing on Shen Zhen Stock Exchange and the lack of study of SMEs sector of Chinese audit market have inspired this work to determine the audit pricing models of these companies.